2017
DOI: 10.5964/ijpr.v11i1.223
|View full text |Cite
|
Sign up to set email alerts
|

Function of attachment hierarchies in young adults experiencing the transition from university

Abstract: An important cornerstone of Bowlby's attachment theory (1969/1997) is the proposal that moving away from parents and toward peers is an indication of healthy development. In this study, we explored the benefit of the shift, not the shift itself, in a sample of emerging adults experiencing a stressful life event (i.e., the transition from university). Although the shift from parents to peers is an important cornerstone of Bowlby's theory, this study is one of the first to test the differential effects of parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
4
0
4
Order By: Relevance
“…This result suggests that attachment to fathers is more significant for exploratory behavior than for reassurance in stressful situations (Grossmann et al, 2002; Di Folco and Zavattini, 2014; Palm, 2014). Overall, these findings suggest that although parents may lose their privileged position in the attachment network as their children mature and form romantic relationships, they continue to fulfill important attachment functions (Scharfe et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…This result suggests that attachment to fathers is more significant for exploratory behavior than for reassurance in stressful situations (Grossmann et al, 2002; Di Folco and Zavattini, 2014; Palm, 2014). Overall, these findings suggest that although parents may lose their privileged position in the attachment network as their children mature and form romantic relationships, they continue to fulfill important attachment functions (Scharfe et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Ce questionnement s'inscrit dans une continuité car, dès le plus jeune âge, l'individu développe des représentations du fonctionnement du système familial dans lequel il est intégré (Minuchin, 1974) et des relations qu'il entretient avec les différents membres de ce système (Miljkovitch, 2009). Ces représentations sont particulièrement prégnantes dans le développement des adultes en émergence, notamment en période de transition (Kins, Beyers, & Soenens, 2012 ;O'Connor et al, 2011 ;Scharfe, Pitman, & Cole, 2017). Bien que s'inscrivant dans une continuité, ces représentations ne sont pas figées et vont être amenées à changer et à évoluer au cours de temps (e.g., Flament, 2001 ;Pietromonaco & Barrett, 2000).…”
Section: Période De Transition Vers L'âge Adulteunclassified
“…Les styles d'attachement développés durant l'enfance par les adultes en émergence entrent en jeu lors de périodes de transition (Kins, Beyers et al, 2012 ;Scharfe et al, 2017).…”
Section: Ajustement Psychosocial Et Styles D'attachementunclassified
See 1 more Smart Citation
“…Indeed, these relationships in adolescence and emerging adulthood can be the most important for a young person's well-being (Amati et al, 2018;Harris & Vazire, 2016;Rubin et al, 2004). Trinke and Bartholomew (1997) highlighted the importance of friends as attachment figures during the transition to adulthood, and Scharfe et al (2017) concluded similar when exploring the role of peers on adjustment to transition from the university. Close friendships are related to numerous developmental aspects, such as identity exploration, self-esteem, conflict management, and social competence in general.…”
Section: Introductionmentioning
confidence: 98%